A model of neurovascular coupling and the BOLD response PART II. Issue 5 (4th April 2017) - Mathias, E. J.; Plank, M. J.; David, T.
Abstract : A mathematical model is developed which describes a signalling mechanism of neurovascular coupling with a model of a pyramidal neuron and its corresponding fMRI BOLD response. In the first part of two papers (Part I) we described the integration of the neurovascular coupling unit extended to include a complex neuron model, which includes the important Na/K ATPase pump, with a model that provides a BOLD signal taking its input from the cerebral blood flow and the metabolic rate of oxygen consumption. We showed that this produced a viable signal in terms of initial dip, positive and negative BOLD signals. In this paper (PART II) our model predicts the variations of the BOLD response due to variations in neuronal activity and indicates that the BOLD signal could be used as an initial biomarker for neuronal dysfunction or variations in the perfusion of blood to the cerebral tissue. We have compared the simulated hypoxic BOLD response to experimental BOLD signals observed in the hippocampus during hypoxia showing good agreement. This approach of combined quantitative modelling of neurovascular coupling response and its BOLD response will enable more specific assessment of a brain region.